The Landscape, Its Narrative Identity and Man’s Well-Being - Brugiatelli, Dr. Vereno (European Journal of Multidisciplinary Studies, 2018)
In this study I intend to put forward a reflection on the landscape and, in particular, on the relationships that man establishes with it. From the European Landscape Convention (Florence, 20.X.2000), which considers the landscape a socio-cultural product, I aim to analyze this concept in order to determine: 1. what the identity of a certain landscape consists of and what constitutes it; 2. the relationship between the identity of the landscape and the identity of its inhabitants; 3. the importance of the identity of the landscape when planning and implementing interventions to safeguard and enhance it; 4. the ethical and cultural bases influencing urban planners and architects when intervening in the landscape; 5. the importance of the landscape to man’s well-being.